Night sky - Drimmer, Stephanie Warren; National Geographic Society (U.S.) (Washington, DC : National Geographic, 2017)
"Information about the stars in the sky for very young children"--
Look up! -- Earth's sidekick -- Twinkle, twinkle -- Stellar space facts -- A home for the sun -- Flying objects -- Spot the dots -- Who's out there? -- Quiz whiz.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Ages 5-8.
K to grade 3.
Print version record and CIP data provided by publisher; resource not viewed.
OverDrive (READ) format features optional read-along narration.
Keywords: Astronomy -- Juvenile literature; Stars -- Juvenile literature; Astronomy; Stars; Electronic books- OSLIS; Juvenile works; Electronic books